Amide proton transfer CEST of the cervical spinal cord in multiple sclerosis patients at 3T. Issue 2 (5th May 2017) - By, Samantha; Barry, Robert L.; Smith, Alex K.; Lyttle, Bailey D.; Box, Bailey A.; Bagnato, Francesca R.; Pawate, Siddharama; Smith, Seth A.
Abstract : Purpose: The ability to evaluate pathological changes in the spinal cord in multiple sclerosis (MS) is limited because T1 ‐ and T2 ‐w MRI imaging are not sensitive to biochemical changes in vivo. Amide proton transfer (APT) chemical exchange saturation transfer (CEST) can indirectly detect amide protons associated with proteins and peptides, potentially providing more pathological specificity. Here, we implement APT CEST in the cervical spinal cord of healthy and MS cohorts at 3T. Methods: APT CEST of the cervical spinal cord was obtained in a cohort of 10 controls and 10 MS patients using a novel respiratory correction methodology. APT was quantified using two methods: 1) APTw, based off the conventional magnetization transfer ratio asymmetry, and 2) ΔAPT, a spatial characterization of APT changes in MS patients relative to the controls. Results: Respiratory correction yielded highly reproducible z‐spectra in white matter (intraclass correlation coefficient = 0.82). APTw signals in normal‐appearing white matter (NAWM) of MS patients were significantly different from healthy controls ( P = 0.04), whereas ΔAPT of MS patients highlighted large APT differences in NAWM. Conclusion: Respiration correction in the spinal cord is necessary to accurately quantify APT CEST, which can provide unique biochemical information regarding disease processes within the spinal cord. Magn Reson Med 79:806–814, 2018. © 2017 International Society for Magnetic Resonance in Medicine.